The Resilience of Catholic Migrant Workers' Marriages: Socio-Religious Challenges in South Malang, Indonesia - Lamatokan, Yohanes Victor Baro Bitan; Raharso, Alphonsus Tjatur (Institut Agama Islam Negeri (IAIN) Manado, 2024)
This study examines the resilience of Catholic migrant workers' marriages in South Malang, Indonesia, within a diverse socio-religious context. The research aims to explore the challenges faced by Catholic couples in maintaining long-distance marriages and to analyze the strategies they employ to preserve marital harmony. Utilizing a qualitative approach with phenomenological methods, this study involves in-depth interviews with two Catholic couples, one of whom works as a migrant worker. The results indicate that couples face dual challenges: economic pressures driving migration and the complexity of maintaining religious identity as a minority. Strategies employed include intensive communication, strengthening faith, and involvement in church communities. Analysis using